2015
DOI: 10.2217/pme.15.37
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Oncology Nurses Concerning Pharmacogenomics

Abstract: Therefore, future research on the assessment of attitudes of oncology nurses concerning pharmacogenomics should incorporate these themes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…A significant barrier to routine PGx implementation in oncology practice is the cost of testing, which was reported in eight studies 21,24,27,31,35,38–41 . Both oncology HCPs and patients voiced their concerns about the cost and lack of health insurance coverage for PGx tests that impede the utilization of PGx screening in routine clinical care, despite high willingness for PGx‐guided oncology treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A significant barrier to routine PGx implementation in oncology practice is the cost of testing, which was reported in eight studies 21,24,27,31,35,38–41 . Both oncology HCPs and patients voiced their concerns about the cost and lack of health insurance coverage for PGx tests that impede the utilization of PGx screening in routine clinical care, despite high willingness for PGx‐guided oncology treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that PGx education is a key driver to promoting PGx integration in clinical oncology. [22][23][24][25][26]32,38 Across studies, most HCPs expressed a high desire for cancer PGx education as part of their continuing professional education. Notably, Dodson undertook a comparison of oncology nurses' knowledge score pre-and post-education intervention and demonstrated that continuing PGx education is effective in improving nurses' short-term knowledge of genomic and PGx information (Table 2).…”
Section: Oncology Pgx Educationmentioning
confidence: 99%
See 3 more Smart Citations